RANCANG BANGUN INTEGRASI TOMBOL EKSPOSI DENGAN LAMPU TANDA RADIASI DAN PENGUNCI PINTU OTOMATIS - Ali Amroji; Ismanto; Novia Legita Maharani (JRI (Jurnal Radiografer Indonesia), 2019)
Background: Generally the use of radiation sign lamp in radiology department hospitals at Jabodetabek area is still manual by pressing button the switch on or off, also the door is opened when the radiation sign lamp are on, although there is no x-ray examination in the room. This often becomes ambiguousby the public. This study aims to minimize ambiguous in order to improve radiation safety by build a miniature automatic integration system with an exposure button with a radiation sign lamp and automatic door lock for indicator radiation safety on a radiology department hospital. Method: This study uses an experimental research method, by build hardware on a miniature that resembles a radiology examination room, then tested the usage function with 3 radiographers as respondents by providing a function test form and the results processes using the formula average. Results: Respondents' answers with an average result of 3.6 showed that this miniature design was successful / able to illustrate the efforts of radiation safety and radiation protection by means of automatic work that was able to minimize the ambiguous of people's understanding of radiation signaling lamps and radiological doors.